2019
DOI: 10.1590/s2175-97902019000118295
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of nanocarriers loaded with Levofloxacin for enhanced antimicrobial activity; physicochemical properties, in vitro release and oral acute toxicity

Abstract: Inorganic and carbon based nanomaterials are widely used against several diseases, such as cancer, autoimmune diseases as well as fungi and bacteria colonization. In this work, Santa Barbara Amorphous mesoporous silica (SBA), Halloysite Nanotubes (HNTs) and Multiwalled Carbon Nanotubes (CNTs) were loaded with fluoroquinolone Levofloxacin (LVF) to be applied as antimicrobial agents. The prepared via adsorption nanocarriers were characterized by Fourier-Transformed Spectroscopy, Scanning Electron Microscopy as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In general, the possible interactions might occur between polymers and drugs molecules can lead to undesirable effects as instability or incompatibility of the formulations (Jayaraj et al, 2010; Siafaka et al, 2019; Siafaka, Okur, et al, 2019; Üstündağ Okur et al, 2019). The study of such interactions can be performed via FT‐IR spectroscopy which is a widely useful technique in pharmaceutical technology (Siafaka et al, 2016; Siafaka, Barmbalexis, & Bikiaris, 2016a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the possible interactions might occur between polymers and drugs molecules can lead to undesirable effects as instability or incompatibility of the formulations (Jayaraj et al, 2010; Siafaka et al, 2019; Siafaka, Okur, et al, 2019; Üstündağ Okur et al, 2019). The study of such interactions can be performed via FT‐IR spectroscopy which is a widely useful technique in pharmaceutical technology (Siafaka et al, 2016; Siafaka, Barmbalexis, & Bikiaris, 2016a).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in the case of n > 1.0 super case II transport is apparent ‘ n ’ is the slope value of log mt/m∞ versus log time curve. When the release mechanism is mainly based on Fickian diffusion, a dimensionless expression of the Higuchi model can be applied (Siafaka et al, 2019; Üstündağ‐Okur et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…54 Through FTIR investigations, some levo bands were observed in the Zn-Al LDH/levo nanocomposite spectrum, which conrmed the successful loading of levo onto the Zn-Al LDH surface, as observed in the appearance of peaks at 2037, 1497 and 1087-1036 cm À1 , which are related to C-O-C, C-O and C-F, respectively. 28,47,50,[54][55][56][57][58] Besides this, some peaks were shied to a lower wavenumber, as shown in Table 2. 3.1.3.…”
Section: Resultsmentioning
confidence: 78%
“…It has been shown in many studies that these criteria are used to select the correct release kinetics [20,31]. In most studies, R 2 has been reported to be the most important criterion for model selection [32,33,34,35]. The highest R 2 , R 2 adjusted and MSC values and the lowest AIC values were used for evaluating for several models.…”
Section: In Vitro Release and Release Kinetic Evaluationmentioning
confidence: 99%